Bio-reducible polycations from ring-opening polymerization as potential gene delivery vehicles. Issue 27 (10th June 2016) - Yu, Qing-Ying; Liu, Yan-Hong; Huang, Zheng; Zhang, Ji; Luan, Chao-Ran; Zhang, Qin-Fang; Yu, Xiao-Qi
Abstract : Bio-reducible polycations were prepared via ring-opening polymerization. These materials have relatively low molecular weights and cytotoxicity but have good DNA condensation ability, transfection efficiency and excellent serum tolerance. Abstract : Synthetic polycations show great potential for the construction of ideal non-viral gene delivery systems. Several cationic polymers were synthesized by the epoxide ring-opening polymerization between diepoxide and various polyamines. Disulfide bonds were introduced to afford the polymers bio-reducibility, while the oxygen-rich structure might enhance the serum tolerance and biocompatibility. The polycations have much lower molecular weights than PEI 25 kDa, but still could well bind and condense DNA into nano-sized particles. DNA could be released from the polyplexes by addition of reductive DTT. Compared to PEI, the polycations have less cytotoxicity possibly due to their lower molecular weights and oxygen-rich structure. More significantly, these materials exhibit excellent serum tolerance than PEI, and up to 6 times higher transfection efficiency than PEI could be obtained in the presence of serum. The transfection mediated byTETA-SS was seldom affected even at a high concentration of serum. Much lower protein adsorption of polycations than PEI was proved by bovine serum albumin adsorption experiments. Flow cytometry also demonstrates their good serum resistance ability.